Occupational Hazards Awareness and Preventive Practices Among Dental Interns Versus Dental Postgraduate at Riyadh Elm University Hospital - M.B.B. Ch. MD. PhD., Dr. Ahmed Sayed Khashaba; AlAnazi, Abdulmohsen Mamdouh; AlDawsari, Omar Mufi; AlQahtani, Meshal Mohammed (International Journal of Innovative Research in Medical Science, 2019)
Background: Dental interns and postgraduates were predisposed to a number of occupational hazards, these includes exposure to infections, percutaneous exposure events, dental materials, radiation, and noise, musculoskeletal disorders, psychological problems and dermatitis, respiratory disorders, and eye problems. Aim of work: To assess the level of occupational hazards awareness and preventive practices among dental interns versus dental postgraduates in Riyadh Elm University. Subject and methods: 100 participants were subjected to a questionnaire that included demographic data, awareness of occupational hazards and safety measures practiced by the study participants. Assessment tools were conducted through calculation of the three rates (accident incidence rate, accident frequency rate and accident severity rate), in addition to, calculation of frequency of each question, scoring degree and grading from weak, moderate to excellent. Results: Out of the 100 participants, 85% were males and 15% were females; 87% of participants were excellent in applying the term preventive practices and the rest of participants were moderate but the difference between the two groups was statistically insignificant (P= 0.103) and nearly equal to each other. However, the majority of participants awareness about occupational hazards and preventive practices were weak and the difference between the two groups was statistically significant (P=0.000). Conclusion: Dentists were exposed to many occupational risks hazarded during work and need more education programs to overcome these occupational hazards.